The Seasonality of Conflict - Guardado, Jenny; Pennings, Steven (World Bank, Washington, DC, 2020)
This paper investigates whether poor employment prospects of potential insurgents help to fuel conflict. The paper provides a new test of this "opportunity cost mechanism" using one of the largest shocks to labor demand in agricultural societies: harvest. Theoretically, the paper shows that because seasonal harvest shocks are temporary and anticipated, they change opportunity costs while keeping the dynamic benefits of fighting constant, yielding unbiased estimates even if those benefits are unobserved. In contrast, many other shocks in the conflict literature are persistent and unanticipated, thus also varying the dynamic benefits of fighting that confound estimates of the opportunity cost mechanism. Empirically, the paper estimates of the effect of harvest shocks on conflict intensity in Afghanistan, Iraq, and Pakistan using subnational variation in the timing and intensity of harvest driven by local climatic conditions. Consistent with the opportunity cost mechanism, the results show that the onset of harvest usually reduces the number of insurgent attacks.